EDTA improves stability of whole blood C-peptide and insulin to over 24 hours at room temperature. - Timothy J McDonald (Public Library of Science (PLoS), 2012)
Introduction C-peptide and insulin measurements in blood provide useful information regarding endogenous insulin secretion. Conflicting evidence on sample stability and handling procedures continue to limit the widespread clinical use of these tests. We assessed the factors that altered the stability of insulin and C-peptide in blood. Methods We investigated the impact of preservative type, time to centrifugation, storage conditions and duration of storage on the stability of C-peptide and insulin on three different analytical platforms. Results C-peptide was stable for at least 24 hours at room temperature in both centrifuged and whole blood collected in K(+)-EDTA and serum gel tubes, with the exception of whole blood serum gel, which decreased to 78% of baseline at 24 hours, (p = 0.008). Insulin was stable at room temperature for 24 hours in both centrifuged and whole blood collected in K(+)-EDTA tubes. In contrast insulin levels decreased in serum gel tubes both centrifuged and whole blood (66% of baseline, p = 0.01 and 76% of baseline p = 0.01, by 24 hours respectively). C-peptide and insulin remained stable after 6 freeze-thaw cycles. Conclusions The stability of C-peptide and insulin in whole blood K(+)-EDTA tubes negates the need to conform to strict sample handling procedures for these assays, greatly increasing their clinical utility.